An alginate-based platform for cancer stem cell research. (June 2016) - Qiao, Shu-pei; Zhao, Yu-fang; Li, Chun-feng; Yin, Yan-bin; Meng, Qing-yuan; Lin, Feng-Huei; Liu, Yi; Hou, Xiao-lu; Guo, Kai; Chen, Xiong-biao; Tian, Wei-ming
Graphical abstract: Abstract: As the primary determinants of the clinical behaviors of human cancers, the discovery of cancer stem cells (CSCs) represents an ideal target for novel anti-cancer therapies (Kievit et al., 2014). Notably, CSCs are difficult to propagate in vitro, which severely restricts the study of CSC biology and the development of therapeutic agents. Emerging evidence indicates that CSCs rely on a niche that controls their differentiation and proliferation, as is the case with normal stem cells (NSCs). Replicating the in vivo CSC microenvironment in vitro using three-dimensional (3D) porous scaffolds can provide means to effectively generate CSCs, thus enabling the discovery of CSC biology. This paper presents our study on a novel alginate-based platform for mimicking the CSC niche to promote CSC proliferation and enrichment. In this study, we used a versatile mouse 4T1 breast cancer model to independently evaluate the matrix parameters of a CSC niche – including the material's mechanical properties, cytokine immobilization, and the composition of the extracellular matrix's (ECM's) molecular impact – on CSC proliferation and enrichment. On this basis, the optimal stiffness and concentration of hyaluronic acid (HA), as well as epidermal growth factor and basic fibroblast growth factor immobilization, were identified to establish the platform for mimicking the 4T1 breast CSCs (4T1 CSCs) niche. The 4T1 CSCs obtained from the platform show increased expression of the genes involved in breast CSC and NSC, as compared to general 2D or 3D culture, and 4T1 CSCs were also demonstrated to have the ability to quickly form a subcutaneous tumor in homologous Balb/c mice in vivo . In addition, the platform can be adjusted according to different parameters for CSC screening. Our results indicate that our platform offers a simple and efficient means to isolate and enrich CSCs in vitro, which can help researchers better understand CSC biology and thus develop more effective therapeutic agents to treat cancer. Statement of Significance: As the primary determinants of the clinical behaviors of human cancers, the discovery of cancer stem cells (CSCs) represents an ideal target for novel anti-cancer therapies. However, CSCs are difficult to propagate in vitro, which severely restricts the study of CSC biology and the development of therapeutic agents. Emerging evidence indicates that CSCs rely on a niche that controls their differentiation and proliferation, as is the case with normal stem cells (NSCs). Replicating the in vivo CSC microenvironment in vitro using three-dimensional (3D) porous scaffolds can provide means to effectively generate CSCs, thus enabling the discovery of CSC biology. In our study, a novel alginate-based platform were developed for mimicking the CSC niche to promote CSC proliferation and enrichment.